(untitled) (Ius Novum, 2019)
The purpose of this paper is to investigate the role of European and Asian regional organizations in monitoring of progress towards SDG 3 and to scrutinize similarities and differences in the previous approach of European and Asian countries to sustainable development goals. In 2015, the UN Agenda for Sustainable Development was adopted. Since then, regional international organizations, including the EU and the ASEAN, have been obliged to include 17 Sustainable Development Goals in their policies. The article focuses on SDG 3, which concerns protecting health and well-being. The article was prepared on the basis of the following research methods: legal dogmatic, systematic and comparative. Attention has been drawn to different approaches towards human health adopted by the EU and the ASEAN, according to which it can be perceived as a human right or a quality important for the whole society and nation. Potential grounds for cooperation in SDG and SDG 3 are also presented. The normative and institutional efforts to achieve the Sustainable Development Goals and to effectively address them are complementary and mutually reinforcing.